تقييم معايير المدرسي و بعض العوامل(الشخصية-الاجتماعية) المحددة لعملية توجيه تلاميذ السنة الأولى ثانوي نحو شعية تقني رياضي من وجهة نظر مستشاري التوجيه و الارشاد بولاية الأغواط دراسة استكشافية - خلافي فاطمة; عمري زبيدة; محمد بوفاتح (My University, 2022)
The purpose this study contained the evaluation of the education and some personal things limited socials, and to evaluate the pupils of the first year to the branch of (matte technic)to the idea of the guidance of in orientation in WELLAYA of LAGHOUAT, also consultation between the differences between of there point of views, and ,also between the difference of their sexes , and to applicat this study we follow this way of studies, we applicator an application whichcontained (37) question, after we accrue this results:  Standards of orientation which applicat nowdays to orient the pupils to the brunch Maths Technic, do not help the operation orientation.  The first personal things which have influence to indicate diser of the pupils to the brunch of math technic and that with the person of (78.86٪).  It has no differences between the answers of the adviser of the orientation in the standards of the orientation, the needs of the brunchtake.  it has difference between the answers of the adviser of orientation and causling, to evaluation the essential factors to indicate the diser s’ pupils to the brunch of math technicwhich take into consideration the diser of the pupils.